Comparison of ultrasound therapy and local steroid injection in rotator cuff tendinitis - Noviar Noviar; A BM Tulaar; Y I Kasjmir; S Sudarsono (Indonesian Journal of Rheumatology, 2011)
Objective: To evaluate the effectiveness of ultrasound therapy compared with local steroid injection for pain relief and movement limitation in rotator cuff tendinitis.Methods: Patients with rotator cuff tendinitis at the rheumatology and rehabilitation outpatient clinic at Cipto Mangunkusumo General Hospital were enrolled in a parallel randomized trial, in which each eligible patient were randomly assigned to one of two groups: one group received 10 sessions of ultrasound therapy given in 2 weeks, the other received a single dose of local steroid injection. Evaluation of the visual analog scale(VAS) was performed in 10 days (5 days for each week: day 1–5 and 8–12), while evaluation of the abduction as well as external and internal rotation range of motion(ROM) was performed twice a week (day 2, 5, 9, and 12). Change in the variables between the two groups at the end of the second week (day 12) was then compared. Results: Thirty patients, divided into two groups consisting of 15 patients each, were recruited in the study. Significant decrease in VAS during the followups was obtained in both groups, slightly earlier in the steroid injection group (day 2; p = 0.041) comparedwith the ultrasound group (day 3; p = 0.001). Significant increase in abduction ROM was achieved at the same rate (beginning at day 5) in both groups. Significant increase in internal rotation ROM was achieved at day 9 in the ultrasound group (p = 0.043) and day 12 in steroid injection group (p = 0.044). The increase in external rotation ROM in both groups was not found to be statistically signifi cant. At the end of the second week, signifi cant difference between the two groups was only shown in the abduction ROM, with higherincrease in the steroid group.Conclusions: Ultrasound therapy provided a comparable effectiveness to steroid injection inalleviating pain and improving ROM in patients with rotator cuff tendinitis.